Bulk metal matrix composite materials with nanoscale fillers - Shcheretskyi, Volodymyr; Zatulovskyi, Andriy (Lviv Polytechnic Publishing House, 2016)
Arming of metal alloys by high strength refractory particles is one of the most common methods for wear resistant, tribological or mechanical properties improving, such materials is called – metal matrix composites. Nanoparticles via mutual contact tend to be agglomerated; they become stable only at micro sizes. Thermo-chemical and mechanical fixation of nanoparticles on the surface of metal powder particles forms micro-nano granules. Such combined micro-nano objects have numerous advantages that allow consolidating them in bulk composite material by extrusion or impregnation methods. Thereby combining foundry and powder approaches, copper and aluminum based composite materials were obtained with uniformly distributed up to 3 weight % of nanoscale components.
Keywords: composites; nano particles; carbides; aluminum; copper; consolidation